The Effect of Regular Exercise on Heart Health - Syafawi, Ishar; Prawibowo, Muhammad; Yanti, Elisa Dwi; Novianti, Reza; Salman, Ali (Program Pascasarjana Universitas Negeri Jakarta, 2025)
This study aimed to examine the effect of regular exercise on heart health among adults aged 25–40 years. The research employed a quasi-experimental design using a pretest–posttest control group model. A total of 40 participants were divided into two groups: an experimental group and a control group. The experimental group performed moderate-intensity aerobic exercise such as jogging and cycling for 12 weeks, three times a week, for 45 minutes per session, while the control group maintained their normal lifestyle without additional exercise. Data were collected through measurements of resting heart rate, blood pressure, and VO₂ max before and after the intervention. A paired sample t-test was used to analyze differences between pretest and posttest results. Findings revealed significant reductions in resting heart rate and blood pressure, along with significant improvements in cardiovascular endurance (p < 0.05). These results demonstrate that regular exercise enhances cardiac efficiency, improves blood circulation, and reduces the risk of cardiovascular diseases. The study recommends consistent aerobic exercise as an effective preventive approach to maintaining heart health and improving adult physical fitness.